Iceland, adventure travel map : revised regularly, waterproof, tear-resistant / National Geographic - National Geographic Maps (Firm) (Evergreen, Colo. : National Geographic Maps, 2015)
Relief shown by contours, shading, and spot heights.; Panel title.; At head of title: National Geographic.; "© 2015 by National Geographic Society . Base data © 2015 Reise Know-How Verlag Peter Rump GmbH D-Bielefeld. Kartographie Huber."; Printed in western/eastern segments.; Includes notes, index of places, location map, color illustrations, and publisher's advertisement.; At head of ISBN barcode: 2015 LC05 Color; 1:465,000